2024
DOI: 10.7150/thno.90187
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-tropic Trojan horses: Using mesenchymal stem cells as cellular nanotheranostics

Ana Rosu,
Behnaz Ghaemi,
Jeff W.M. Bulte
et al.

Abstract: Various classes of nanotheranostics have been developed for enhanced tumor imaging and therapy. However, key limitations for a successful use of nanotheranostics include their targeting specificity with limited off-site tissue accumulation as well as their distribution and prolonged retention throughout the entire tumor. Due to their inherent tumor-tropic properties, the use of mesenchymal stem cells (MSCs) as a “Trojan horse” has recently been proposed to deliver nanotheranostics more effectively. This review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 163 publications
0
2
0
Order By: Relevance
“… 85 , 86 Other well-studied molecules, such as tumor necrosis factor-α (TNF-α), IL-6, and hypoxia-inducible factor 1-alpha (HIF-1α), provide further insight into MSCs’ tumor-homing properties. 87 However, it should also be borne in mind that the immunosuppressive and angiogenic properties of MSCs could, in turn, heighten tumorigenic risks, 88 presenting significant challenges for the clinical translation of MSCs as antitumor therapy. Additionally, their migration and homing efficiency post-intravenous injection is insufficient, thereby necessitating the development of more effective strategies, such as the combination with click chemistry and bio-orthogonal reactions, to enhance their targeting to tumor sites.…”
Section: Hydrogels For Cell Therapymentioning
confidence: 99%
“… 85 , 86 Other well-studied molecules, such as tumor necrosis factor-α (TNF-α), IL-6, and hypoxia-inducible factor 1-alpha (HIF-1α), provide further insight into MSCs’ tumor-homing properties. 87 However, it should also be borne in mind that the immunosuppressive and angiogenic properties of MSCs could, in turn, heighten tumorigenic risks, 88 presenting significant challenges for the clinical translation of MSCs as antitumor therapy. Additionally, their migration and homing efficiency post-intravenous injection is insufficient, thereby necessitating the development of more effective strategies, such as the combination with click chemistry and bio-orthogonal reactions, to enhance their targeting to tumor sites.…”
Section: Hydrogels For Cell Therapymentioning
confidence: 99%
“…Mesenchymal stem cells (MSCs), also known as "mesenchymal stromal cells", are the cornerstone, hope, and fear of modern cancer therapy [1]. According to MSCs' inherent tumor-tropic properties, their use as a "Trojan horse" for more effective delivery of encapsulated drug forms into tumors has been proposed [2][3][4][5][6]. Nevertheless, a growing number of oncology studies have demonstrated that MSCs possess dual characteristics related to cancer development.…”
Section: Introductionmentioning
confidence: 99%